All-Optical Binary to Decimal Converter with Dark-Bright Soliton Conversion Control - Suphanchai Punthawanut; Preecha P. Yupapin; Xaythavy Louangvilay; Somsak Mitatha (My University, 2011)
In this paper we propose all-optical binary to decimal converter with dark-bright soliton conversion control. The input logic '0' and '1' are performed by dark and bright soliton, respectively. By using the dark-bright soliton conversion behavior with in the π/2 phase shift device, we can use the drop and though port output for represent decimal number output for each binary input. This is a simple and flexible scheme for performed logic switching system, which can be used in advanced complex logic.
Keywords: Decimal; Optical Network Technologies